Absorción de aceites presentes en aguas residuales de lubricadora, utilizando bagazo de caña de azúcar pretratado con cera de abeja - Segovia Carrera, Jennifer Estefania (2019)
Lubricants and washing machines generate high pollution rates in Ecuador, this is in line with the demand and existence of cars, where the common pollutant, in its wastewater, is the used lubricants in which hazardous chemical compounds of difficult degradation are present, such as: heavy metals. The mishandling of these wastes can create a problem on a large scale by causing damage to living beings and their environment. That is why, in the present investigation, a treatment is proposed by means of adsorption of oils present in wastewater from lubricator, using sugarcane bagasse pretreated with beeswax; for this, the characteristics and optimal proportions of each component were determined in order to achieve the best removal of oils present in a sample of water that contains 3570 mg / l of contaminant load, through experimentation in batch tests, followed by variation in percentage of the mixture to analyze the adsorption behavior. In addition, the equilibrium function of the mixture was studied through the use of adsorption isotherms: among them, the linear isotherm, Langmuir isotherm, Freundlich isotherm and Redlich - Peterson isotherm with the help of regression analysis. Also, to know the properties of the substrate used, a physical characterization of the different size fractions was performed, where moisture, ash, organic matter, densities and porosity were calculated. The sugarcane bagasse pretreated with beeswax presented favorable characteristics for the treatment of adsorption of oils in the wastewater, since it had an efficiency of 61 percent with an optimal mixture of granulometry sugarcane bagasse 1.59 mm and 15 percent beeswax. After carrying out the analyzes of different models, the Redlich - Peterson isotherm was the one that had a greater adjustment of experimental data to the determined line with 92 percent.